Math and Arithmetic
Algebra
Calculus

# What equals 1 cos squared x divided by cos squared x?

234

###### 2012-05-01 00:32:52

1. Anything divided by itself always equals 1.

๐
0
๐คจ
0
๐ฎ
0
๐
0

## Related Questions

2 x cosine squared x -1 which also equals cos (2x)

Multiply both sides by sin(1-cos) and you lose the denominators and get (sin squared) minus 1+cos times 1-cos. Then multiply out (i.e. expand) 1+cos times 1-cos, which will of course give the difference of two squares: 1 - (cos squared). (because the cross terms cancel out.) (This is diff of 2 squares because 1 is the square of 1.) And so you get (sin squared) - (1 - (cos squared)) = (sin squared) + (cos squared) - 1. Then from basic trig we know that (sin squared) + (cos squared) = 1, so this is 0.

If x = sin &theta; and y = cos &theta; then: sin&sup2; &theta; + cos&sup2; &theta; = 1 &rarr; x&sup2; + y&sup2; = 1 &rarr; x&sup2; = 1 - y&sup2;

tan^2(x) Proof: cos^2(x)+sin^2(x)=1 (Modified Pythagorean theorem) sin^2(x)=1-cos^2(x) (Property of subtraction) cos^2(x)-1/cos^2(x)=? sin^2(x)/cos^2(x)=? (Property of substitution) sin(x)/cos(x) * sin(x)/cos(x) = tan(x) * tan(x) (Definition of tanget) = tan^2(x)

[sin - cos + 1]/[sin + cos - 1] = [sin + 1]/cosiff [sin - cos + 1]*cos = [sin + 1]*[sin + cos - 1]iff sin*cos - cos^2 + cos = sin^2 + sin*cos - sin + sin + cos - 1iff -cos^2 = sin^2 - 11 = sin^2 + cos^2, which is true,

Sin squared is equal to 1 - cos squared.

sin2 x = (1/2)(1 - cos 2x) cos2 x = (1/2)(1 + cos 2x) Multiplying both you get (1/4) (1 - cos2 2x) Which is equal to (1/4) (1 - (1/2) (1 + cos 4x) = (1/8) (2 - 1 - cos 4x) = (1/8) (1 - cos 4x) Or If it is the trigonomic function, sin squared x and cosine squared x is equal to one

sin cubed + cos cubed (sin + cos)( sin squared - sin.cos + cos squared) (sin + cos)(1 + sin.cos)

cos2(theta) = 1 so cos(theta) = &Acirc;&plusmn;1 cos(theta) = -1 =&gt; theta = pi cos(theta) = 1 =&gt; theta = 0

The answer is 1. sin^2 x cos^2/sin^2 x 1/cos^2 cos^2 will be cancelled =1 sin^2 also will be cancelled=1 1/1 = 1

(1+cosx)(1-cosx)= 1 +cosx - cosx -cos^2x (where ^2 means squared) = 1-cos^2x = sin^2x (sin squared x)

2cos2x - cosx -1 = 0 Factor: (2cosx + 1)(cosx - 1) = 0 cosx = {-.5, 1} x = {...0, 120, 240, 360,...} degrees

There is a hint to how to solve this in what is required to be shown: a and b are both squared.Ifa cos &theta; + b sin &theta; = 8a sin &theta; - b cos &theta; = 5then square both sides of each to get:a&sup2; cos&sup2; &theta; + 2ab cos &theta; sin &theta; + b&sup2; sin&sup2; &theta; = 64a&sup2; sin&sup2; &theta; - 2ab sin &theta; cos &theta; + b&sup2; cos&sup2; &theta; = 25Now add the two together:a&sup2; cos&sup2; &theta; + a&sup2; sin&sup2; &theta; + b&sup2; sin&sup2; &theta; + b&sup2; cos&sup2; &theta; = 89&rarr; a&sup2;(cos&sup2; &theta; + sin&sup2; &theta;) + b&sup2; (sin&sup2; &theta; + cos&sup2; &theta;) = 89using cos&sup2; &theta; + sin&sup2; &theta; = 1&rarr; a&sup2; + b&sup2; = 89

Yes and the answer is 1 squared equals 1

How is it possible that the value of cosecant is less than 1 (2/7)?

Rewrite 1/cos x as (cos x)-1 and use chain rule.

This is geometry/trigonometry, not calculus. That said, cos 2a = .3 The property you need: cos 2u = 1 - 2sin2u = 2cos2u - 1 Using the first equality: cos(2a) = 1 - 2sin2a Let u = a (.3) = 1 - 2sin2a Substitute cos(2a) = .3 .7 = sin2a Subtract .3 from both sides, get rid of negative sign sin a = .71/2 Square root both sides a = sin-1 .71/2= .991156 Not a special angle, use calculator.

cot(x)=1/tan(x)=1/(sin(x)/cos(x))=cos(x)/sin(x) csc(x)=1/sin(x) sec(x)=1/cos(x) Therefore, (csc(x))2/cot(x)=(1/(sin(x))2)/cot(x)=(1/(sin(x))2)/(cos(x)/sin(x))=(1/(sin(x))2)(sin(x)/cos(x))=(1/sin(x))*(1/cos(x))=csc(x)*sec(x)

###### Math and ArithmeticCalculusTrigonometry

Copyright ยฉ 2020 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.